Mimbar Literasi Aktivisme 5.0 dalam Rangka Peringatan Hari Pendidikan Nasional 2026: Penguatan Kedaulatan Digital Mahasiswa melalui Integrasi IMTAQ dan IPTEK - fitra yuda (JURNAL MASYARAKAT NEGERI ROKANIA, 2026)
Abstract: The community service activity entitled Mimbar Literasi Aktivisme 5.0 was organized to strengthen students’ digital sovereignty awareness during the commemoration of National Education Day 2026. The activity addressed the challenge of global technology hegemony through the integration of IMTAQ and IPTEK, with emphasis on data governance, algorithmic literacy, cyber hygiene, responsible artificial intelligence, and ethical digital activism. This article uses a descriptive participatory approach based on activity documents, seminar materials, visual documentation, and reflective discussion. The activity was held at SMA 3 Tanah Putih, Rokan Hilir, on 16 May 2026, involving students, student organization leaders, facilitators, and speakers. The results show that the seminar created a practical learning space for students to understand digital sovereignty as the ability to use, evaluate, secure, and create technology responsibly. The main outputs were a five-layer digital sovereignty framework, a personal digital audit activity, and a 90-day campus action roadmap consisting of digital literacy, ethical AI learning, cybersecurity habits, and local innovation initiatives. The activity indicates that computer science knowledge becomes more meaningful when connected to moral values, social responsibility, and public communication. The limitation of this report is the absence of a quantified pre-test and post-test instrument, so the findings are presented as process-based outcomes. Future activities need to include measurable competency assessment and longer mentoring after the seminar.